A Re-Assessment of the Diatom Communities in Perdido Bay and Pensacola Bay in Response to the Deepwater Horizon Oil Spill - Adhikari, Arjun (My University, 2012)
A primarily taxonomical study was conducted to assess the distribution of diatoms after the Deepwater Horizon oil rig explosion in the Gulf of Mexico, April 20, 2010. The study is focused on the possible effects of the Deepwater Horizon oil spill on diatoms. Sampling was conducted on bimonthly basis for six months at Perdido Bay and Pensacola Bay, starting 24 September, 2010, and ending 10 May, 2011. Samples were collected from the surface as net plankton, sediment, and as whole water. Global Positioning System (GPS) was used to keep a record of exact locations of sampling. Physical characteristics such as water temperature, dissolved oxygen (DO), light intensity, salinity, and turbidity were taken at the time of sampling. Samples were preserved in Lugol’s iodine to avoid further growth and were transported back to the lab for further testing. The primary objectives of the study was diatom community characterization, comparing datasets with previous studies, and recording the number of deformed diatom valves possibly attributed to the Gulf of Mexico oil spill. A total of 524 species were encountered contributing to 90 genera. Species diversity was measured using the Shannon-Wiener index. Relative abundance of species was also calculated by counting at-least 400 valves in one transect per slide for each sample. To characterize the community structure, PRIMER-E ver. 5.0 was used to assess the Bray-Curtis similarity index and to perform multidimensional scaling, and principal component analysis. The results showed a high diversity and variability in the Perdido/Pensacola Bay ecosystem and an insignificant number of the deformed valves (<< 0.01%).
A thesis by Arjun Adhikari
Keywords: diotoms; oil spill; Deepwater Horizon; Pensacola Bay; Gulf of Mexico; Species Diversity